Gender and exemplarity in medieval and early modern Spain - Morrás, María,Sanmartín Bastida, Rebeca,Kim, Yŏnsu (Brill, 2020)
Gender and Exemplarity in Medieval and Early Modern Spain gathers a series of studies on the interplay between gender, sanctity and exemplarity in regard to literary production in the Iberian peninsula. The first section examines how women were con¬strued as saintly examples through narratives, mostly composed by male writers; the second focuses on the use made of exemplary life-accounts by women writers in order to fashion their own social identity and their role as authors. The volume includes studies on relevant models (Mary Magdalen, Virgin Mary, living saints), means of transmission, sponsorship and agency (reading circles, print, patronage), and female writers (Leonor López de Córdoba, Isabel de Villena, Teresa of Ávila) involved in creating textual exemplars for women.
9789004438446